A broadened innovation support for mutual benefits: Academic engagement by universities as part of technology transfer. (1st June 2015) - Jonsson, Lars; Baraldi, Enrico; Larsson, Lars-Eric
While the spin-out funnel has received professional support to enhance its effects in most western universities, much less attention has been paid to the possibility to enhance the effects of academic engagement (i.e. publications, meetings and collaborative research among others) in the knowledge exchange activities of universities. By using the case of Uppsala University as a reference, the aim of this paper is to describe how a holistic organization for innovation support can be managed to create mutual benefits both for the external organizations, the society, the university itself as well as its faculties. Four key elements seem to be of importance to the effectiveness of the support organization: (1) the alignment with selected goals and activities of the university; (2) the recruitment strategy, with innovation support officers possessing double competences; (3) building trust, among all stakeholders and (4) the introduction of specific tools to enhance the effects of academia-industry interactive activities.We conclude that a holistic approach provides many benefits for the university as well as for the external organizations involved. An important finding is that the commercialization funnel and academic engagement are not two separate tracks but actually seem to lever each other's so that commercialization seems to be important to build trust and stimulate the academic engagement as well as for embedding the university innovation support units in the industrial network, and the later may result in concrete commercialization projects. Our results also indicate that this broader strategy for innovation support seems to appeal better to the fields of humanities and social science compared to traditional tech-transfer. Still, many results need to be codified, and more research is needed to fully understand the impact of academia-industry interactions over time.